Aerobic capacity of professional soccer players before and after COVID-19 infection - Parpa, K.; Michaelides, M. (Scientific Reports, 2022)
This investigation aimed to assess the aerobic capacity of professional soccer players pre-and post-COVID-19 infection. Twenty-one division-1 elite soccer players (age 24.24 ± 5.75 years, height 178.21 ± 5.44 cm, weight 74.12 ± 5.21 kg) participated in this study. This observational study compared the same players' aerobic capacity pre-, and 60-days post COVID-19 recovery. The statistical analysis demonstrated that the infected players had significantly lower VO2max values [t(20) = 5.17, p < 0.01, d = 0.613 (medium effect)], and significantly lower VO2 values at respiratory compensation point (RC) [t(20) = 2.97, p < 0.05, d = 0.39 (small effect)] after recovery. Furthermore, results indicated a significantly lower running time (RT) on the treadmill [t(20) = 4.84, p < 0.01, d = 0.46 (small effect)] when compared to the results that were obtained before they got infected. In addition, velocity at VO2max (VVO2max) was significantly lower [t(20) = 2.34, p < 0.05, d = 0.41 (small effect)] and the heart rate values at ventilatory threshold (VT) [t(20) = -2.79, p < 0.01, d = 0.55 (medium effect)] and RC [t(20) = -3.72, p < 0.01, d = 0.52 (medium effect)] were significantly higher post-recovery. The aforementioned findings indicate that post COVID-19 soccer players may not reach full recovery at two months. Therefore, our results highlight that further adaptations and improvements are needed with regard to aerobic capacity before soccer players return to professional games.